High prevalence of hepatitis E and rat hepatitis E viruses in wastewater in Gothenburg, Sweden - Marianela Patzi Churqui; Margarita Ghaleb; Timur Tunovic; Miriam Frankal; Lucica Enache; Kristina Nyström; Martin Lagging; Hao Wang (One Health)
Hepatitis E virus (HEV) and Rat Hepatitis E virus (RHEV), recognized for their zoonotic potential, pose significant public health concerns. Our previous research identified both viruses in effluent wastewater in Gothenburg, Sweden. However, there are lingering inquiries regarding the prevalence and genetic diversity of these viruses in influent wastewater, as well as the utility of wastewater surveillance in elucidating their community circulation dynamics. To address these knowledge gaps, we conducted weekly collection of wastewater samples at the Rya wastewater treatment plant in Gothenburg throughout 2023. The concentrations of HEV and RHEV were quantified using quantitative polymerase chain reaction (qPCR). Additionally, two semi/nested-PCR were utilized to amplify viral strains. Furthermore, HEV strains from patients within the same region, as well as other regions in Sweden in 2023, were incorporated into the analysis. Remarkably, we observed a high prevalence of HEV (86%) and RHEV (98%) in wastewater samples, with the majority of HEV sequences identified as subtype 3c/i (9/12). In contrast, HEV subtype 3f was the most sequenced among clinical patient samples (6/12). Notably, previously unreported HEV-3b and unclassified strains were detected in wastewater. Almost all RHEV strains (20/21) were clustered into European groups, with none of the RHEV genetically close to strains previously found in human cases. The notable discordance in prevalence and identified subtypes of HEV-3 in wastewater compared to clinical samples suggests either a significant underdiagnosis of HEV infections or differences in viral loads and shedding durations among humans between HEV-3 subtypes. This underscores the urgent need for improved diagnostic techniques and heightened awareness of HEV transmission dynamics. Furthermore, the consistent detection of RHEV in wastewater underscores the necessity for further investigations to assess the potential role of RHEV in hepatitis cases of unknown etiology, given that most currently available clinical diagnostic assays fail to detect RHEV.